Acceptance of Malaysian’s consumers toward availability of red palm oil products / Aisarizzat Azizi - Azizi, Aisarizzat (Faculty of Plantation and Agrotechnology, 2017)
Palm oil is an edible vegetable oil derived from the mesocarp (Reddish pulp) of oil palm Elaeis guineensis. It is naturally reddish in colour because of a high beta-carotene content which is sources of vitamin A & E. A study was conducted to identify the determinant that influences the acceptance of Malaysian’s consumer toward availability of red palm oil products. A survey method used for collecting data. The questionnaire was distributed to 80 respondents that consist of consumer in Malaysia. The result were interpreted by hypothesis testing, descriptive analysis, spearman correlation and multiple regression by using Statistical package for Science Computer Software (SPSS) version 20. The R square (Coefficient of determined value) 0.988 indicated that 98.8% of the variation of acceptance red palm oil product was explained by the government, awareness and knowledge, 1.2% is explain by other factor that has not studied. The result from multiple regression found that the Government factor influence dependent variable which is 0.736 (beta value = 0.736, p<0.05). To determine the crucial factor that influence dependence variable, the stepwise method are carry out in multiple regression analysis. It is a method combined forward and backward selection technique. It will remove non-significant variable from the model and the Government factor was determined as most influence factor on dependence variable. After that, Spearman correlation analysis was carried out to determine the relationship between independence and dependence variables. For government variable it was computed there was relationship between acceptance and government effort on red palm oil products. There was a strong positive relationship between the two variables, r = 0.990, n = 80, p = 0.000. The relationship was strong because the Government factor was a vital variable on acceptance of consumers. The significant value (p value) was 0.000 less than 0.05 thus reject H0. To be concluding, there was a relationship between the government effort and acceptance of consumers toward availability of red palm oil products.